Epigenetics of lifestyle - Párrizas, Marcelina; Gasa, Rosa; Kaliman, Perla (Bentham Books, 2012)
Refers to the way in which the environment in the wide sense participates in the regulation of gene expression. This volume is a simplified source of information for both undergraduate and working professionals interested in lifestyle medicine and life sciences in general.